Cognitive function surrounding resection of nonfunctioning pituitary adenomas with suprasellar extension: A prospective matched-control study. (June 2017) - Hendrix, Philipp; Griessenauer, Christoph J.; Hans, Elisa; Simgen, Andreas; Oertel, Joachim; Karbach, Julia
Highlights: Nonfunctioning pituitary adenomas may cause cognitive deficits in subsets of cognitive domains. The risk for cognitive deterioration due to surgical therapy is low. Within the first months after surgery, mild cognitive impairments may completely resolve. Abstract: Objective: Patients suffering from pituitary adenomas may experience cognitive dysfunctions due to hormonal imbalance or suprasellar tumor extension displacing neural structures. Progressively enlarging or symptomatic nonfunctioning pituitary adenomas with suprasellar extension are frequently resected. The literature on neurocognitive performance surrounding resection of these lesions is sparse. Methods: A prospective matched-control study was conducted to investigate the impact of nonfunctioning pituitary adenomas with suprasellar extension on preoperative and postoperative cognitive performance. Controls were matched for age, sex, handedness, education, and profession. The neurocognitive test battery included perceptual speed, executive function, visual-spatial and verbal working memory, short- and long-term memory, verbal fluency, fluid intelligence, anxiety, and depression. Results: Ten patients and 10 healthy controls were matched. Median suprasellar tumor extension scored 8 mm, compression of frontal lobe parenchyma was present in all cases. Median sagittal tumor diameter was 21 mm. Preoperatively, patients scored worse in perceptual speed and short-term memory tasks. All patients underwent surgical resection either through a transnasal, transsphenoidal approach or a supraorbital frontolateral keyhole approach. The short-term memory deficit disappeared one week after surgery. Perceptual speed recovered within two months after surgical therapy. None of the patients experienced worsening of cognitive function. Routine postoperative imaging at six months did not reveal displacement of neural structures or surgery-related complications in any of the patients. Conclusion: Patients suffering from nonfunctioning pituitary adenomas with suprasellar extension may experience preoperative impairments in some neurocognitive domains that resolve within two months after surgery. The risk for cognitive deterioration with surgery appears to be low.